Transformasi Sosial Pendidikan - ahmad sopian (Raudhah - Proud To Be Professional, 2020)
Social transformation and education can not be avoided, there are changes that are fast and some are slow. Two factors that make the change come from within the community itself and some from outside. What comes from the community are population growth, relations with other cultures, new discoveries, technology and so on. While from the outside is the surrounding environment, the influence of other cultures and so on.Social transformation and educational is planned and some unplanned. The planned changes will be carried out by the agent of change to obtain the desired conditions of the agent of change. Agents of change for example education, government, companies, development and so on.Every time a transformation occurs, the community will try to adjust to these changes. But if a society is closed from transformation or rejected, there will be cultural backwardness